valuation of the Effectiveness of the Virtual Reality Technologies Comprehensive Rehabilitation Program Application: a Prospective Cohort Study of 59 Patients with Rotator Cuff Injury - Vasiliy A. Kolyshenkov; Andrey N. Prosvirnin (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2023)
AIM. To evaluate the effectiveness of the comprehensive rehabilitation program for patients with rotator cuff injury using virtual realitytechnology.MATERIAL AND METHODS. The study examined 59 patients, 29 (49.2%) male and 30 (50.8%) female, the average weight was 79[70.00;87.50] kg, the average height was 1.72 [1.63;1.78] m, the average age was 48 [32.00;54.00] years, randomly divided into twogroups. The control group consisted of 30 patients, including 16 men and 14 women, the average age was 47.00 [27.00;54.00] years,the average height and weight were 1.71 [1.63;1.78] m and 77.50 [70.50;88.25] kg, respectively. Patients of the control group receiveda standard rehabilitation methodology. The study group consisted of 29 people, 13 men and 16 women, mean age 48 [39.50;56.50]years, mean height 1.72 [1.62;1.78] m, mean weight 81.00 [70.00;86.00] kg, who received classes with the inclusion of virtual realitytechnologies against the background of the standard method.RESULTS AND DISCUSSION. The study showed a positive dynamics of pain syndrome, an improvement of the functional state of theshoulder joint according to the results of the DASH questionnaire, an increase in the volume of the shoulder joint motions. The averageindicators of dynamic strength and muscular endurance and performance in the "inward/outward rotation" test increased by 58% and68.5%. In the " adduction/abduction" tests, the strength indicators of patients with rotator cuff tears increased by 67.5%, and muscleendurance and performance by an average of 82.3%. According to the results of isokinetic testing, the growth of strength values in the"extension / flexion" test was 64.5%, and muscle endurance and performance were 79%.CONCLUSION. The inclusion of virtual reality technologies at the stage of medical rehabilitation of patients with rotator cuff injuriescan significantly reduce shoulder pain, improve upper extremity functioning, increase joint range of motion, and significantly improvestrength, muscular endurance and performance.